2017
DOI: 10.1144/qjegh2016-106
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory studies of Miocene limestone in Sri Lanka

Abstract: Geologically 10% of Sri Lanka is made up of Miocene limestone, which covers the northern and northwestern coastal belt of the island. It is used as a raw material for various industries, but at present only cement and lime are used for the construction industry. Therefore the author carried out a series of laboratory tests to determine the mechanical properties of limestone in Sri Lanka, with the aim of determining the suitability of Miocene limestone as aggregate for the construction industry. Borehole sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The authors claimed that the presence of these minerals could over a period of time cause strength failure. In the study by Pang et al (2010) and Jayawardena (2017), the LA performance of 25% and 33-38%, respectively, of limestone showed that the strength depends on the content of calcite mineral. Both authors claimed that limestone may not be suitable for surface layer of road pavement.…”
Section: Secondary and Accessory Mineralsmentioning
confidence: 98%
“…The authors claimed that the presence of these minerals could over a period of time cause strength failure. In the study by Pang et al (2010) and Jayawardena (2017), the LA performance of 25% and 33-38%, respectively, of limestone showed that the strength depends on the content of calcite mineral. Both authors claimed that limestone may not be suitable for surface layer of road pavement.…”
Section: Secondary and Accessory Mineralsmentioning
confidence: 98%
“…Miocene limestone, widely distributed sedimentary rock in Sri Lanka is a highly porous and permeable rock and not a strong rock. But some highly consolidated and compacted parts are strong [8].…”
Section: Resultsmentioning
confidence: 99%